Negotiating Haqq al-Ibtikar and State Patent Law: A Socio-Legal Study of Maslahah and Intellectual Property among Indonesian Muslim SMEs - lilis, lilis diah sugiarti; Hidayat, Agi Attaubah; Anwari, Amalia Nur; Zulvia, Ransya Ayu; Kholid, Muhamad (DIKTUM: Jurnal Syariah dan Hukum, 2026)
Background: Indonesia’s 64 million SMEs drive 61% of national GDP yet face critical barriers in patent protection due to costly procedures, legal complexity, and low IP literacy. Purpose: This study analyzes systemic gaps in Indonesia’s patent law (Law No. 13/2016) hindering SME innovation and proposes inclusive legal reforms. Methods: A normative juridical approach examines statutory frameworks, case studies, and secondary data from academic literature (2017–2025) Results: Key findings reveal: (1) High patent registration costs (up to IDR 20.9 million) exclude 87% of SMEs; (2) First-to-file systems disadvantage grassroots innovators; (3) Enforcement remains inaccessible due to lengthy litigation (avg. 30 months) and minimal ADR mechanisms. Implication: Structural reforms are urged: specialized IP courts, tiered fee subsidies, and SME-tailored simple patents. Indonesia’s model could inform Global South patent policies. Originality: This research introduces the inclusive patent framework—integrating open licensing, communal IP rights, and university-SME collaboration—as a novel juridical paradigm for equitable innovation.